From Theory to Practise: Applying Constructivism, Behaviorism, and UDL in Diverse Classrooms - Salmiah, Salmiah; Nabila, Nabila; Sok, Vann (Journal of Educational Teaching and Trends, 2025)
Contemporary classrooms face increasing diversity in student needs, learning styles, and cultural backgrounds, necessitating pedagogical approaches that bridge theoretical foundations with practical implementation. While constructivism, behaviorism, and Universal Design for Learning (UDL) are widely studied, their synergistic application in real-world settings remains underexplored, particularly in resource-constrained environments. This study examines how these three theoretical frameworks can be integrated to create inclusive, adaptive learning environments. It evaluates their combined impact on student engagement, knowledge retention, and equity across diverse classroom contexts. A mixed-methods approach was employed, analyzing 35 peer-reviewed studies (2015–2023) from Scopus and ERIC databases, alongside case studies of 12 schools in Indonesia, Finland, and South Africa. Data were triangulated through classroom observations, teacher interviews, and pre/post-intervention assessments. UDL-enhanced constructivist strategies increased participation by 40% in heterogeneous classrooms, while behaviorist techniques improved skill mastery in structured settings. Key success factors included teacher training (p<0.01) and flexible curriculum design. Rural schools achieved 28% higher outcomes by localizing UDL principles despite technological limitations. The deliberate integration of these theories addresses the “one-size-fits-all” dilemma, proving that contextually adapted blends outperform isolated approaches. Policymakers should prioritize teacher capacity-building to scale this model.